Epic hikes of the world : explore the planet's most thrilling treks and trails. - Lonely Planet Global Limited (Carlton, Victoria ; Oakland, CA : Lonely Planet Global Limited, 2018)
Highlights hiking routes in thirty countries worldwide, from New Zealand to Peru, discussing one-day jaunts, urban trails, and month-long hikes.
At head of title: Lonely planet.
Includes index.
Keywords: Hiking -- Guidebooks; Trails -- Guidebooks